Peculiarities of Calculation of Vortex Dust Collectors by Determining its Geometry (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article deals with issues related to the need to extract expensive dusts from process gases. For this purpose, a dry method of cleaning is recommended, against the use of a wet method. The principle of operation of a dust collector with counter swirling flows is described, based on the interaction of two swirling gas flows created in one apparatus. The results obtained for the operation of these devices give every reason to consider them competitive